PENJATUHAN SANKSI PIDANA DI BAWAH BATAS MINIMUM KHUSUS DALAM UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - ROMULUS, SH A.2021141042, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2016)
ABSTRACTThe thesis is the imposition of criminal sanctions under the minimum limit is specialized in Law Number 35 Year 2009 on Narcotics (Studies in Kuala Kapuas District Court's Decision No. 103 / Pid.Sus / 2015 / PN KIK). The method used in this research is a normative approach. From the results of this thesis research we concluded that existence of sentences below the minimum threshold specific provisions of the law in the case of narcotic crime committed by judges, including judges PN Kuala Kapuas, can not be justified by the principle of legality (nulla poena sine lege) which in which an element of legal certainty, for the principle of nulla poena sine lege, which means